2011
DOI: 10.5248/116.381
|View full text |Cite
|
Sign up to set email alerts
|

First report of Morganella compacta (Agaricales, Lycoperdaceae) from South America

Abstract: Abstract-Morganella compacta is recorded for the first time from South America. This species is found in Northeastern Brazil growing on sandy soil of dune ecosystems. Detailed descriptions, illustrations of basidiomata and basidiospores SEM are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Morganella arenicola was recently confused with M. compacta, which was registered for the first time for South America (Barbosa et al, 2011). However, a number of characteristics remain discrepant and make the real identity of the Brazilian collections suspicious.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morganella arenicola was recently confused with M. compacta, which was registered for the first time for South America (Barbosa et al, 2011). However, a number of characteristics remain discrepant and make the real identity of the Brazilian collections suspicious.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a comparative study of the characteristics analyzed confirmed that the Brazilian specimens were distinct from the New Zealand specimens of Morganella compacta. The specimens considered by Barbosa et al (2011) actually belong to a distinct taxon, denominated here by M. arenicola. In addition to the Atlantic Forest, the distribution of this new taxon was widened to the Amazon Forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mainly cited from New Zealand, L. compactum has also been reported from Costa Rica (Calonge et al 2005), and from Brazil (Barbosa et al 2011); however, Brazilian specimens were misidentified. (Demoulin 1972a) and L. echinatum (3 6 mm long) (Demoulin 1982;Calonge 1996); also, the basidiospores are distinctive between them, the Brazilian species are mostly punctate [A] (although B can be found) versus the basidiospores verrucose [C] in these two species (Demoulin 1972a;1982).…”
Section: Figmentioning
confidence: 99%